1993
DOI: 10.1126/science.8493534
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV-1 DNA and Messenger RNA in Individual Cells by PCR-Driven in Situ Hybridization and Flow Cytometry

Abstract: Human immunodeficiency virus type-1 (HIV-1) DNA and messenger RNA sequences in both cell lines and blood obtained directly from HIV-1-infected patients were amplified by polymerase chain reaction and hybridized to fluorescein-labeled probes in situ, and the individually labeled cells were analyzed by flow cytometry. After flow cytometric analysis, heterogeneous cell populations were reproducibly resolved into HIV-1-positive and -negative distributions. Fluorescence microscopy showed that the cellular morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(156 citation statements)
references
References 24 publications
6
150
0
Order By: Relevance
“…8 The virus was replication competent but apparently had not been exposed to the selection pressure exerted by the therapy, implying that the virus was not replicating. Early in situ polymerase chain reaction (PCR) studies on harvested lymphoid tissues [9][10][11] or peripheral blood cells 9 revealed viral RNA in a small percentageoften less than 10% -of cells in which viral DNA was present, indicating that in most cells the provirus is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…8 The virus was replication competent but apparently had not been exposed to the selection pressure exerted by the therapy, implying that the virus was not replicating. Early in situ polymerase chain reaction (PCR) studies on harvested lymphoid tissues [9][10][11] or peripheral blood cells 9 revealed viral RNA in a small percentageoften less than 10% -of cells in which viral DNA was present, indicating that in most cells the provirus is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find it necessary to use other strategies to obviate this problem, such as the use of multiple primer sets, extra-long products, overlapping primers, post-PCR fixation with paraformaldehyde or biotinylated primers. 28,29 A post-hybridization wash of 62°C was used. This is higher than in published protocols but was found to eliminate background without significantly decreasing detectable product.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the actual cells that are infected has been carried out using in situ RT-PCR to detect single copies of HIV-1 in infected cells. 18,[21][22][23][24][25][26][27][28] Previous in situ RT-PCR studies (presumably on subtype B) have localized the virus to lymph node germinal centres [29][30][31] either as free virus 30 or in association with CD21 þ follicular dendritic cells or macrophages, 18,25,26,[28][29][30][31][32][33] but not interdigitating dendritic cells. 32 It has been proposed that CD4 þ lymphocytes become infected as they contact follicular dendritic cells in transit through lymph node germinal centers.…”
Section: Discussionmentioning
confidence: 99%